The Influence of Problem Based Learning (PBL) Model on Student Learning Outcomes in Mathematics Learning Materials Building Cube Space and Beam in Class V SDN 060907 Medan Maimun District - Dinda Sulistia; Arrini Shabrina Anshor (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the effect of the problem based learning (PBL) model on student learning outcomes in learning mathematics on the material of cubes and blocks in class V SDN 060907 Medan Maimun District This study used a quasi-experimental design (quasi experimental design). The participants involved in this study were students in class VA and VB SD Negeri 060907 Medan Maimun District, with a total of 20 VA students and 19 VB students. The total number of participants was 39 students. Specifically, VA and VB students have the same learning ability characteristics and there is also no superior class at SD Negeri 060907 Medan Maimun District. The population in this study were all VA and VB class students at SD Negeri 060907 Medan Maimun District. The determination of the class to be used as the sample in this study was taken from the population, namely VA class students as the experimental class and VB class as the control class. The data collection techniques used in this study are: Tests, Documentation. Based on the results of the research that has been done, the results of the research based on hypothesis testing can be obtained tcount 5,643 and ttable 1,668 so that the result is tcount > ttable (5,643 > 1,668) meaning that H1 is accepted and H0 is rejected. So, it can be concluded that there is an influence of the problem based learning model on the learning outcomes of fifth grade students at SDN 060907 Medan Maimun District. This research was conducted on fifth grade students at SDN 060907 Medan Maimun District with a population of 39 students in the experimental class and control class with 20 VA students in the experimental class and 19 VB students in the control class.